The Benefits of Android Applications for an Independent Learning in Learning English Language - Faiz Ushbah Mubarok; Atiqah Nurul Asri (English Language Education Study Program Universitas Maritim Raja Ali Haji, 2021)
Due to the pandemic condition, we rely more on the technology usage. Technology presents us plentiful advantages and features in the teaching and learning. Specifically in smart phones, android nowadays offer numerous applications of language learning in Play Store. This article shows the benefits of Android applications namely Duolingo, Busuu, Rosetta Store, and Memrise in learning English language. These apps enhance the user’s four language skills mastery using games, riddles and other various ways. By learning language independently, students may also their cognitive, meta-cognitive and affective skills. It aids learners to gain their goals in a fun and enjoyable ways. Further, it is also beneficial in terms of improving students’ motivation and confidence, easy and simple, practical and entertaining, and sustainability.